Reflection on MOOC Design in Palestine - Saida Affouneh (Athabasca University Press, 2018)
This paper will share Discover Palestine, an interdisciplinary Massive Online Open Course (MOOC) and the first MOOC to be created in Palestine, by the E-Learning Centre, Faculty from the Department of Geography, and Department of Tourism and Archaeology from An-Najah National University in Palestine. The paper traces the process of development of the Discover Palestine MOOC from its early inception as a cross institutional online course, to its current delivery and engagement with a global and diverse group of learners. Using a descriptive case study design and thematic analysis, the reflective experiences of four course team members involved as facilitators/designers in the design and delivery of the MOOC are shared. Three key themes, namely, “Informing pedagogies including delivery methods,” “A commitment to a national cause,” and “Teacher presence,” are presented and contextualized with data evidence. The findings share not only the hurdles the Discover Palestine team had to navigate during the MOOC development, but more importantly, how academic collaborations promoting open education practices offer powerful tools for the reciprocal exchange of knowledge, not least in shifting mindsets, and offering opportunities for shared fields of understanding to be realized in revealing creative, cultural practices, as well as lost histories.